Molecular identification and Characterization of Viral Particles Present In a Shrimp Pond: A Metagenomic Approach - Narasimhudu.m (Dept:of Aquatic Animal Health Management School of Aquaculture And Biotechnology, 2017)
Abstract- Viruses are considered as very significant biological entities on the global ecosystem. Viruses control so many factors like bacterial growth, biogeochemical cycles as well as the nutrient cycles. Though many investigations have focused on the significance of viruses on the aquatic ecosystem, the information regarding their diversity, relationships andgenes in an aquaculture pond is still scarce.The present study was mainly concentrated on exploring the viral diversity present in shrimp farms employingmetagenomic approach. In the present study two samples were collected; one the water sample and another sediment sample from two different shrimp cultured ponds located in Cheppanam and Aroor areas respectively. Sediment sample was processed by filtration flocculation resuspension (FFR) method.Viral particles were purified and concentrated employing several stages of filtration and chemical flocculation. The presence of viral particles was confirmed at each step of purification and concentration employingepifluorescence microscopy using SYBR Gold. Presence of numerous viral particles confirmed the concentration and purity of the viral filtrate. Finally, viral nucleic acid was extracted using QIAampMinElute Virus Spin kitand the viral nucleic acids were subjected to Next Generation Sequencing at Genotypic Technology, Bangalore. The result from Next generation sequencing lab showed the presence of 75 % Synechococcusphages and remaining 25 % with different types of phages.Interestingly, no pathogenic viruses could be amplified from the shrimp farm, though the sample was collected from a farm that recorded a recent WSSV outbreak.